Pyroptosis-related genes GSDMB, GSDMC, and AIM2 polymorphisms are associated with risk of non-small cell lung cancer in a Chinese Han population - Zhang, Xia; Liu, Rongfeng (Frontiers in Genetics, 2023)
Background: Pyroptosis is essential for the remodeling of tumor immune microenvironment and suppression of tumor development. However, there is little information available about pyroptosis-related gene polymorphisms in non-small cell lung cancer (NSCLC). Methods: Six SNPs in the GSDMB, GSDMC and AIM2 were genotyped in 650 NSCLC cases and 650 healthy controls using a MassARRAY platform. Results: Minor alleles of rs8067378, rs2305480, and rs77681114 were associated with a lower risk of NSCLC (p<0.005), whereas rs2290400 and rs1103577 were related to an increased risk (p<0.00001). Moreover, rs8067378-AG/GG, rs2305480-GA/AA, and rs77681114-GA/AA genotypes were associated with a decrease in NSCLC risk (p<0.005). In contrast, the TC/CC genotypes of rs2290400 and rs1103577 were associated with an elevated NSCLC risk (p<0.0001). Based on the analysis of genetic models, minor alleles of rs8067378, rs2305480 and rs77681114 were related to reduced risk of NSCLC (p<0.05); whereas rs2290400 and rs1103577 were related to increased risk (p<0.01). Conclusion: Our findings provided new insights into the roles of pyroptosis-related genes in NSCLC, as well as new factors to be considered for assessing the risk of developing this cancer.